2015
DOI: 10.1111/hsc.12263
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of barriers to physical activity among overweight and obese patients with type 2 diabetes in Iran

Abstract: The objective of this study was to identify common barriers to physical activity practice among overweight/obese patients with type 2 diabetes in Iran and their associations with physical activity level. In this cross-sectional study, 146 overweight/obese volunteers with type 2 diabetes were recruited from diabetes clinics in Tabriz, Iran, between July 2012 and March 2013. A Persian version of the long-format International Physical Activity Questionnaire was used to assess physical activity level. A 12-item st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…It has been recommended that moderate to vigorous physical activity can reduce the risk of chronic diseases such as diabetes and its complications [65][66][67]. Health counsellors should address these barriers to increase the patients' adherence to physical activity as the recommendations [41]. Our current results showed that physical activities (PC 2 ) were associated with a decreased risk of diabetes.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…It has been recommended that moderate to vigorous physical activity can reduce the risk of chronic diseases such as diabetes and its complications [65][66][67]. Health counsellors should address these barriers to increase the patients' adherence to physical activity as the recommendations [41]. Our current results showed that physical activities (PC 2 ) were associated with a decreased risk of diabetes.…”
Section: Discussionmentioning
confidence: 52%
“…To the best of our knowledge, few studies have used PCA to address the physical activity. For example, one study conducted exploratory principal components factor analyses of influences on physical activity instrument [40]; another study used PCA to extract the factors of barriers with physical activity level [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of 5167 persons in Canada aged 15–79 years found that educational attainment, family income, self-rated health, intentions, self-efficacy scores, perceived barriers, perceived health benefits, and facility availability were factors associated with physical activity behaviors 12. A cross-sectional study of overweight and obese persons in Iran with type 2 diabetes mellitus identified barriers to physical activity that included negative attitude toward physical activity, discouragement, physical problems, cost, and environmental factors 13. Barriers more specific to older obese and overweight persons with multiple chronic conditions, have not been identified.…”
Section: Introductionmentioning
confidence: 99%